Risk and preventive factors for heat illness in radiation decontamination workers after the Fukushima Daiichi Nuclear Power Plant accident. Issue 4 (31st October 2015) - Kakamu, Takeyasu; Hidaka, Tomoo; Hayakawa, Takehito; Kumagai, Tomohiro; Jinnouchi, Takanobu; Tsuji, Masayoshi; Nakano, Shinichi; Koyama, Kikuo; Fukushima, Tetsuhito
Abstract : Risk and preventive factors for heat illness in radiation decontamination workers after the Fukushima Daiichi Nuclear Power Plant accident: Takeyasu Kakamu, et al . Department of Hygiene and Preventive Medicine, Fukushima Medical University School of Medicine Objective: The aim of this study was to reveal factors related to heat illness in radiation decontamination workers and determine effective preventive measures. Methods: A self‐administered questionnaire was sent to 1, 505 radiation decontamination workers. The questionnaire included age, sex, duration of decontamination work, previous occupation, education provided by employers regarding heat illness, preventive action against heat illness, and subjective symptoms of heat illness during work. We included 528 men, who replied and answered all questions, in the statistical analysis. Subjective symptoms of heat illness were categorized as "no symptoms", "Grade I" and "Grade II" according to severity. A multiple linear regression model was used to determine the factors associated with the severity of heat illness. Results: The mean age of the subjects was 47.6 years old (standard deviation: 13.4). Of the 528 workers, 316 (59.8%) experienced heat illness symptoms (213 at Grade I and 103 at Grade II). The results of the stepwise selection revealed that age, outdoor manual labor, adequate sleep, use of a cool vest, and salt intake were selected as preventive factors, whereas living in a company dormitory or temporary housing, wearing light clothing, and consuming breakfast were selected as risk factors for heat illness. Conclusions: Both working conditions and living environment are associated with heat illness in radiation decontamination workers. Type of housing and sleep are also strongly related to heat illness during work. Employers should consider not only the working conditions of the employee but also the employee's daily living conditions, in order to prevent heat illness.